Unraveling an uncommon encounter: hypokalemic periodic paralysis with Brugada phenocopy amidst hypokalemia - Razan Dankar; Salim Barakat; Elie El-Charabaty; Syed Salman Hamid Hashmi; Suzanne E. El Sayegh (European Journal of Case Reports in Internal Medicine)
Introduction: Hypokalemic periodic paralysis (HPP) presents a diagnostic challenge due to the painless muscle weakness it causes. This case discusses a patient with HPP along with electrocardiogram (ECG) findings of Brugada phenocopies (BrP) in the setting of hypokalemia. A review of the literature showed that it is the seventh documented example of BrP induced by hypokalemia alongside HPP. Case description: A 43-year-old man presented to the emergency department with lower limb weakness. He attributed his symptoms to a substantial meal consumed after breaking his Ramadan fast, recalling a similar episode following heavy meals in the past. The patient was alert and oriented but demonstrated reduced strength in both upper and lower limbs. ECG revealed a Brugada type 1 pattern. Laboratory analysis revealed hypokalemia (2.5 mmol/l), elevated creatine kinase (326 U/l), and normal thyroid function. Following potassium supplementation, his symptoms resolved, and his ECG normalized. Discussion: HPP occurs in the context of increased carbohydrate intake, potentially leading to rapid insulin release and activation of Na-K ATPase, enhancing cellular potassium absorption and lowering serum potassium levels. Symptoms range from weakness and fatigue to severe neuromuscular weakness and cardiac arrhythmias. Investigating hypokalemia requires excluding hypomagnesemia, thyroid function tests, and metabolic acidosis/alkalosis before considering HPP. Management involves gradual oral potassium repletion to avoid the risk of hyperkalemia associated with intravenous administration. Conclusion: Clinicians should consider including HPP in differential diagnoses of patients presenting with weakness. In this case, electrophysiological evaluation suggested Brugada pattern induced by hypokalemia, which resolved with potassium supplementation.